Odpowiedzi

Najlepsza Odpowiedź!
2010-02-20T19:31:02+01:00
A)(x+2)²(x²-2x+4) = ( x²-2x+4)(x²-2x+4)= x⁴-2x³+4x²+4x³-8x²+16x+4x²-8x+16= x⁴+2x³+8x+16

b)(3x-1)²(9x²+3x+1) = (9x²-6x+1) (9x²+3x+1) = 81x⁴+27x³+9x²-54x³-18x²-6x+9x²+3x+1= 81x⁴-27x³-3x+1

c)(x²+5x+25)(x-5)²= (x²+5x+25)(x²-10x+25)= x⁴-10x³+25x²+5x³-50x²+125x+25x²-250x+625= x⁴-5x³-125x+625

d) (x+2)(x²+4)(x-2)=(x³+4x+2x²+8)(x-2)= x⁴-2x³+4x²-8x+2x³-4x²+8x-16= x⁴-16

e)(x-1)(x²+x+1)(x³+1)=(x³+x²+x-x²-x-1)(x³+1)= (x³-1)(x³+1)=xdo szóstej-1

f)(x+2)(x⁴+4x²+16)(x-2) =(x+2)(x-2)(x⁴+4x²+16)= (x²-4)(x⁴+4x²+16)=
x do szóstej+4x⁴+16x²-4x⁴-16x²-64=x do szóstej-64
1 5 1